Masked Uncontrolled Hypertension Is Accompanied by Increased Out-of-Clinic Aldosterone Secretion. Issue 2 (February 2021) - Siddiqui, Mohammed; Judd, Eric K.; Zhang, Bin; Dudenbostel, Tanja; Carey, Robert M.; Oparil, Suzanne; Calhoun, David A.
Abstract : Masked uncontrolled hypertension (MUCH) in treated patients is defined as controlled office blood pressure (BP) but uncontrolled out-of-clinic ambulatory BP. Previously, we have shown that patients with MUCH have evidence of heightened out-of-clinic sympathetic nervous system activity. The aim is to test the hypothesis that MUCH patients have higher aldosterone secretion compared with patients with true controlled hypertension. Two hundred twenty-two patients were recruited after having controlled office BP readings at ≥3 clinic visits. Patients taking MR (mineralocorticoid receptor) antagonists and epithelial sodium channel blockers were excluded. All patients were evaluated by clinic automated office BP and morning serum aldosterone and plasma renin activity. Out-of-clinic ambulatory BP monitoring and 24-hour urinary aldosterone, catecholamines, and metanephrines were also measured. Sixty-four patients had MUCH, and the remaining 48 patients had true controlled hypertension. MUCH patients had significantly higher out-of-clinic levels of 24-hour urinary aldosterone, catecholamines, and metanephrines compared with true controlled hypertension. The 2 groups did not differ in serum aldosterone, plasma renin activity, or aldosterone-renin ratio collected in clinic. In addition, 32.8% of MUCH patients had high out-of-clinic 24-hour urinary aldosterone (≥12 µg) but normal clinic serum aldosterone (<15 ng/dL) and aldosterone-renin ratio (<20). Further, in correlation matrix analysis, higher 24-hour urinary catecholamines and metanephrines were associated with higher 24-hour urinary aldosterone and plasma renin activity levels in MUCH patients. Patients with MUCH have higher out-of-clinic urinary aldosterone levels compared with patients with true controlled hypertension. This study suggests that patients with MUCH likely have higher out-of-clinic sympathetic nervous system tone increases aldosterone secretion mediated by increased renin release that may contribute to their higher out-of-clinic BP.